(untitled) (Journal of Economic Research & Business Administration, 2015)
The article deals with the analysis of current practice of financial accountability in oil and gas sector according to foreign standards. During recent years the reforming of National Financial Reporting Standards became more active as the existing practice of accountancy in Kazakhstan doesn’t meet in full the needs of external customers in providing them with the information about operation of a company. As a result companies report their financial statements using standards of financial accountability of some foreign countries or International Financial Reporting Standards. The article considers the following questions: a survey of standards of financial accountability used by Kazakhstani oil companies for their stockholders and investors; analysis of current practice on International Accounting Standards in oil and gas companies; review on Generally Accepted Accounting Principles in the USA concerning accounting procedure in oil and gas extraction; development prospects of national standards and regulations of accounting procedure in oil and gas extraction.